Broad inhibition of transmission frequency in multilayered dielectric one dimensional photonic crystal nanostructure - VINOD CHACKO; Sonia Bansal; Aurangzeb khurram Hafiz (International Journal of Science and Engineering, 2019)
We report  the omnidirectional reflection (ODR) in one dimensional photonic crystal (PC) structure consisting of alternate layers of  Cryolite (Na3AlF6) as material of low refractive index and Germanium (Ge) as material of high refractive index. The effects of the thickness of   layers and incidence angles on the spectral reflectance have been investigated using transfer matrix method (TMM).  The proposed structure gives  broad inhibition of transmission frequencies within a wide range of wavelengths in the visible-near IR region (600 nm- 850 nm) which can be tuned according to the design parameters. We observe that cryolite based photonic crystal structure can be used as a good candidate for wavelength filter or broad reflector in the near infrared spectrum which is very useful in many imaging sensors in the field of optical technology